Taking mirrors as mirrors in Greek archaeology - Dietrich, Nikolaus (Art style, 2021)
Art Style | Art & Culture International Magazine Abstract With Eduard Gerhard’s Etruskische Spiegel (1843-1897), bronze mirrors come to be among the earliest classes of objects to have been published in a systematic and extensively illustrated corpus within (classical) archaeology in the mid- nineteenth century. By making available archaeological material to scholars who had hitherto based their knowledge of ancient cultures mainly on written sources, such illustrated corpora constitute a kind of ‘material turn’ avant la lettre within classical scholarship. At the same time, however, these same corpora also initiated a process of de-materialisation of their objects: by substituting them for two- dimensional depictions, they often focused exclusively on areas with pictorial decoration, thereby turning functional material objects into sources for ancient art history. In a first part of this paper, I would like to follow these inherent dialectics in the publication of archaeological material by examining the example of bronze mirrors. In a second part, which is focused mainly on a mid-fifth century BC Greek caryatid mirror in New York (Metropolitan Museum of Art 1972.118.78), I try to ‘restore’ to these Greek mirrors the material aspects that were neglected in past scholarship, using these sophisticated instruments of female cosmetics mainly as sources for the reconstruction of the history of Greek sculpture. Without forgetting the place of mirrors in Greek literature and philosophy, the discussion shall focus on the material affordances of mirrors, and above all their power of reflection and ability to produce an image. The (syn-) aesthetic experience of seeing oneself, put back on centre-stage, will thereby shed new light on those mostly erotic iconographies with which mirrors were adorned.